Development and Molecular Cytogenetic Characterization of Cold-Hardy Perennial Wheatgrass Adapted to Northeastern China - Yan, Wei; Jin, Xin; Jiang, Bo; Qi, Xiaoyue; Chen, Yaxin; Li, Xinling; Liu, Xiaoqiang; Ren, Yongkang; Cui, Lei; Song, Qingjie; Li, Hongjie; Friebe, Bernd; et al. (Frontiers in Plant Science, 2020)
Cold-hardy perennial wheatgrass plays an important role in the use of barren land for farming, soil and water conservation, variety improvement, and also for increasing grass yield. By crossing octoploid tritelytrigia (2n=8x=56, AABBDDEE) with Thinopyrum intermedium (2n=6x=42, StStJJJSJS), we developed 34 lines of perennial wheatgrass from F1 to F6 generations, which had vigorous regrowth and cold hardiness. The cold-hardy, perennial wheatgrass lines were well-adapted to the cold environment and developed root and rhizomes, with a longevity between 5 to 11 years and a better seed set. Some of them maintained wheat chromosomes beneficial for breeding perennial wheat. Molecular cytogenetic analysis demonstrated that the Th. intermedium chromosomes contributed the most to the synthetic genome of the wheatgrass hybrids and were associated with the perennial growth habit and winter hardiness. They were also preferentially maintained and transmitted to the progenies. Some wheat chromosomes were also transmitted from the F1 to F6 generations, although they were eliminated in each life cycle of the wheatgrass hybrids. The numbers of wheat and Th. intermedium chromosomes affected seed set and perennial growth habit. Seed set increased with the establishment of a more balanced genomic constitution in later generations. The cold-hardy and perennial wheatgrass lines were produced, which can be the starting point of domestication effort aimed at producing well-adapted ground cover plants under extreme environments.